One life [compact disc, unabridged] - Rapinoe, Megan, 1985-; Brockes, Emma (Penguin Audio, 2020)
Megan Rapinoe, Olympic gold medalist and two-time Women's World Cup champion, has become a galvanizing force for social change; here, she urges all of listeners to take up the mantle, with actions big and small, to continue the fight for justice and equality. Using anecdotes from her own life and career, from suing the United States Soccer Federation alongside her teammates over gender discrimination to her widely publicized refusal to visit the White House, Rapinoe discusses the obligation people all have to speak up, and reveals the impact they have on their own communities.